Children orphaned by HIV and AIDS in middle childhood in Potchefstroom, Northwest: The role of a social worker. Issue 8 (17th November 2018) - Nkomo, Thobeka S.; Dube, Nkosiyazi; Khosa, Priscalia
ABSTRACT: The effects of HIV and AIDS have devastated families and communities in South Africa. The scourge has also left many children orphaned in the country. Given the vulnerability of orphaned children, social workers are in the forefront of ensuring that these children are cared for and protected from any harm. Hence, the purpose of this paper was to explore the role of a social worker in issues related to children orphaned by AIDS in their middle childhood. This study was situated within a qualitative research paradigm utilizing purposive, non-probability sampling of 10 participants recruited from Potchefstroom in the Northwest Province of South Africa. A semi-structured interview schedule was employed as a research tool, and in-depth one-on-one interviews were adopted as the method of data collection. A thematic content analysis was used to analyze the data collected during the interviews. The main findings point towards the need to educate children about HIV and AIDS and to empower their caregivers. The primary conclusion drawn from this study is that social workers play various key roles which contribute towards the well-being of orphaned children. Recommendations are posed in relation to social work service providers, government interventions, and future research.